(untitled) (Research, Society and Development, 2020)
Objective: To evaluate the control of HIV / AIDS offered by Primary Health Care through the perspective of higher education professionals. Method: Cross-sectional study of non-probabilistic sampling for the convenience of nurses, doctors and dentists inserted in PHC in Palmas, Tocantins through the application of an electronic questionnaire between the months of August and November 2018. The data were consolidated and analyzed by frequency. Results: Regarding the rapid tests for HIV / AIDS, 99.2% reported offering to partners of diagnosed people and 95.3% performed pre-test and post-test counseling. Regarding the management of HIV, 93% conduct an active search for people whose diagnosis was positive and did not return to receive the result, while 80.3% conduct an active search for their partners. Conclusion: The actions of education, prevention, diagnosis and treatment, although existing, still have a long way to go, as a point of investment in professional qualification for adequate assistance.